(3HMhK GdJShjb (B/s - (3GdOjhg Lj, CHj SYjOs ((3YeGf(B: s (3OGQ GdMGeO ddfTQ(B, s, 2001)
(3eaghe hCgejI HMhK GdJShjb(B- (3HMhK GdJShjb hGJNGP GdbQGQGJ(B- (3JUeje GLQGAGJ GdHMK GdJShjbj(B- (3GdeTcdI heMMGJgG aj GdHMK GdJShjbj (B-(3GdHjGfGJ GdKGfhjI(B- (3GdHjGfGJ GdChdjI (B-(3GdYjfGJ(B-(3MLe GdYjfI(B- (3GdGSJHjGf(B((3GdGSJbUGA(B)- (3GdbjGS hGdHMK(B-(3JMdjd GdHjGfGJs
Keywords: (3COGQI GdeHjYGJs; (3GdJShjbs